2021
DOI: 10.12928/optimum.v11i1.4017
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Financial Inclusion and Macroeconomic on Foreign Direct Investment (FDI) Flows in The Organization of Islamic Cooperation (OIC) Countries

Abstract: Foreign capital flows are important factors in the development of sustainable economies, especially in developing countries such as the OIC countries. Lately, the rapid development of the financial sector and macroeconomic stability became a serious concern by foreign investors, where financial inclusion and macroeconomics played an important role in attracting direct foreign capital flows (FDI). The study aims to investigate the role of financial inclusion and macroeconomic variables on the foreign direct flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The Tobit regression however cannot take care of possible sources of endogeneity in our model resulting from either double causality between the financial inclusion variable and other explanatory variables like economic growth and trade. In essence, the literature has equally argued that financial inclusion explains economic growth (Van et al, 2021) and globalization (Andiansyah, 2021). There is therefore the need to implement a methodology that corrects this econometric bias.…”
Section: 2model Specification and Regression Methodologymentioning
confidence: 99%
“…The Tobit regression however cannot take care of possible sources of endogeneity in our model resulting from either double causality between the financial inclusion variable and other explanatory variables like economic growth and trade. In essence, the literature has equally argued that financial inclusion explains economic growth (Van et al, 2021) and globalization (Andiansyah, 2021). There is therefore the need to implement a methodology that corrects this econometric bias.…”
Section: 2model Specification and Regression Methodologymentioning
confidence: 99%
“…Additionally, the number of ATMs per 100,000 adults was 12.6 on average in 2010, which increased to be 26 ATMs in 2020 4 (which means one ATM for each 3846 adults), and the global average is 61.3 ATMs per 100,000 in 2020 5 which means the lower middle-income group of countries still far from the global average. Surprisingly, the lower middle-income group of countries have dissimilar situation regarding FD.…”
Section: Problem Of the Studymentioning
confidence: 99%
“…According to the above findings, Fixed Effects Model will be used. Getting back to table (5), it is found that:…”
Section: π˜π’Šπ’•=𝜷𝟎+πœ·πŸπ—πŸπ’Šπ’•+πœ·πŸπ—πŸπ’Šπ’•+β‹―+πœ·π’Œπ—π’Œπ’Šπ’•+π’†π’Šπ’•(𝟏) π˜π’Šπ’•=πœ·πŸŽπ’Š+πœ·πŸπ—πŸπ’Šπ’•+πœ·πŸπ—πŸπ’Šπ’•+β‹―...mentioning
confidence: 99%
“…To obtain specification for delving into the effects of composite financial inclusion index on economic growth, this study draws on Kim et al [ 15 ] and Andiansyah [ 67 ] and begins with a long-run panel specification as: where Ο† = intercept, Ξ· 1 βˆ’ Ξ· 9 = long-run panel coefficients, t = 1, 2, …, = T , i = 1, 2, …, = N , u = error term of the model following identically and independently normal distribution ( i . i .…”
Section: Model Specificationmentioning
confidence: 99%
“…assumption, and all other variables hold the same meaning as explained before. Except for the rule of law, which is augmented to control for institutional quality on growth, the choice of other explanatory variables is based on recent empirical studies (see, inter alia , [ 27 , 67 – 70 ]). Moreover, it is expected that the signs of Ξ· 1 , Ξ· 2 , Ξ· 4 , and Ξ· 7 > 0, the signs of Ξ· 3 , Ξ· 6 , and Ξ· 9 < 0 and the sign of Ξ· 5 to be a-priori indeterminate; that is, based on the advancement of institutional quality in high-income and upper middle-income economies, it may show positive effects on growth, whilst a negative sign is expected in low-income economies due to deteriorating institutional quality.…”
Section: Model Specificationmentioning
confidence: 99%